Effect of GGBFS on setting, workability and early strength properties of fly ash geopolymer concrete cured in ambient condition - Nath, Pradip; Sarker, Prabir (ELSEVIER, 2014)
Most of the previous works on fly ash-based geopolymers were on the properties of concrete hardened by heat curing, which is considered as a limitation for cast in situ applications at low ambient temperatures. This study aimed to achieve fly ash-based geopolymers suitable for curing without elevated heat. The results show that fly ash based geopolymer concrete for curing in ambient condition can be proportioned for desirable workability, setting time, and compressive strength using ground granulated blast-furnace slag (GGBFS) as a small part of the binder. Inclusion of GGBFS with Class F fly ash helped achieve setting time and compressive strength comparable to those of ordinary Portland cement (OPC).